Chronic thalamic recordings for idiopathic generalized epilepsy and Lennox–Gastaut syndrome: Ictal and interictal electrophysiological findings - Katie L. Bullinger; Angela N. Crudele; Martha J. Morrell; Lise Johnson (Epilepsia Open)
Abstract Objective To leverage RNS® System chronic thalamic EEG recordings to compare ictal and interictal thalamic electrophysiology in idiopathic generalized epilepsy (IGE) and Lennox–Gastaut Syndrome (LGS). Methods As part of ongoing clinical trials in IGE and LGS, intracranial EEG data were acquired from the centromedian nucleus (CM) bilaterally. Ictal recordings were evaluated by trained epileptologists for preictal and ictal onset patterns. The number of detections and the frequency characteristics of interictal and ictal activity were compared across groups. Results Ictal activity was clearly observed in the CM in IGE and LGS. Detections of interictal epileptiform activity and electrographic seizures were more frequent in LGS. Interictal frequency peaks had similar characteristics across cohorts, although low frequencies were more frequent in LGS. All participants with LGS had 2 or more ictal onset patterns. Most often, onset patterns were similar bilaterally. However, 20% of participants had some seizures with different onset patterns on the right and left, and 50% had some seizures that were unilateral. Low voltage fast activity was the most common onset pattern, followed by bursts of polyspikes and then rhythmic <13 Hz activity. In IGE participants, rhythmic <13 Hz activity was the most common ictal onset pattern; spike and wave was the next most common onset pattern. Two additional onset types were observed: polyspike onset and high amplitude delta followed by low amplitude fast activity onset. Onset patterns were generally consistent within an individual; only 20% of participants had multiple seizure onset types. Significance Differences in interictal background are consistent with the known phenotypes of IGE and LGS. Furthermore, CM recordings of ictal activity in both cohorts support the feasibility of closed‐loop stimulation, with detection settings programmed according to each individual's seizure onset pattern. Plain Language Summary The RNS® System was used to record brain activity from the thalamus in people with idiopathic generalized epilepsy (IGE) and Lennox–Gastaut Syndrome (LGS). Seizure‐related activity was detectable in the thalamus in both groups, with detections of abnormal activity more frequent in LGS. LGS participants often had varied seizure onset patterns, while seizure onset patterns were more consistent in IGE. These findings align with known differences between IGE and LGS and suggest that thalamic recordings can guide personalized seizure detection. This supports the potential for using closed‐loop brain stimulation tailored to individual seizure patterns to improve epilepsy management.